PENGEMBANGAN E-LKPD BERBASIS OUTDOOR EDUCATION UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA SISWA SEKOLAH DASAR - Ni Putu Setia Pradnyani; I Gede Astawan; Ni Ketut Desia Tristiantari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is based on problems related to the limitations of digital media, such as Electronic Student Worksheets (E-LKPD) as a learning media that aligns with the analysis of needs, student characteristics, and the low understanding of science concepts among elementary school students. The purpose of this study is to describe the validity, practicality, and effectiveness of outdoor education-based E-LKPD. This study uses the ADDIE development model with data collection methods in the form of questionnaires and tests. The data analysis methods used in this study are qualitative descriptive analysis and quantitative descriptive analysis. Meanwhile, the effectiveness of outdoor education-based E-LKPD is measured using a one group pretest-posttest design involving 35 students. The research results indicate that: (1) the media validation results obtained an average score of 4,6 from content experts and 4.7 from media experts, which fall into the very good category; (2) the practicality of the E-LKPD was obtained through teacher response assessments and student response assessments, which achieved average scores of 4,88 and 4,50 respectively, indicating that both scores fall into the very practical category; (3) the effectiveness test results using a paired t-test showed a significance value of 0.000, less than 0,05, which means there is a significant difference between pre-test and post-test scores after the treatment using the E-LKPD media. Thus, the use of outdoor education-based E-LKPD is effective in enhancing elementary school students’ understanding of science concepts.